Evaluation of Cardiac Function by Two-Dimensional Speckle Tracking Echocardiography in Ulcerative Colitis Patients - ÇİNÇİN, AHMET ALTUĞ; KANİ, HALUK TARIK; ATAŞ, HALİL; SARI, İBRAHİM; SÜNBÜL, MURAT; TİGEN, MUSTAFA KÜRŞAT (SPRINGER, 2014)
Purpose Although ulcerative colitis (UC) shows obvious similarities with other autoimmune diseases, cardiac consequences have not adequately introduced. The aim of our study was to evaluate left ventricular (LV) function in UC patients by using novel echocardiographic parameters. Results Forty-five UC patients (mean age 37, 18 female) and 90 age-and sex-matched healthy volunteers (mean age 40, 38 female) included in the study. The mean disease activity score according to partial Mayo score was 2.16 +/- 2.13. Mean global longitudinal strain (GLS) and global longitudinal strain rate (GLSR) measurements were significantly lower (-21.16 +/- 2.71 vs. -23.36 +/- 3.34; p < 0.001 and -1.33 +/- 0.24 vs. -1.43 +/- 0.24; p = 0.037, respectively), whereas global circumferential (-22.67 +/- 3.66 vs. -23.37 +/- 3.99; p = 0.140) and global radial strain (43.07 +/- 8.58 vs. 44.12 +/- 9.32; p = 0.545) measurements of the LV were similar in patients with UC compared with controls. The correlation coefficient (r) between GLS and partial Mayo score was -0.578 (p < 0.001). Conclusion Our study suggests that systolic cardiac deformation values are impaired in UC patients. Reduced GLS and GLSR might be an early indicator of cardiac involvement in this population.
Keywords: Echocardiography; Ulcerative colitis; Inflammatory bowel disease; Speckle; Strain; INFLAMMATORY-BOWEL-DISEASE; LEFT-VENTRICULAR DYSFUNCTION; GLOBAL LONGITUDINAL STRAIN; MAGNETIC-RESONANCE; SYSTEMIC-SCLEROSIS; DIABETES-MELLITUS; HEART-FAILURE; FOLLOW-UP; DIAGNOSIS; THERAPY